Revision of Flabelligera Sars, 1829 (Polychaeta: Flabelligeridae) - Salazar-Vallejo, Sergio I. (Zootaxa, 2012)
Flabelligera Sars, 1829 is the type genus for Flabelligeridae de Saint-Joseph, 1894 and includes species common in tem-perate or cold waters in the world oceans. Together with Flabelliderma Hartman, 1969 they are the only genera whoseneurohooks have multiarticulate handles and bending crests. However, Flabelliderma species differ because they formlarge notopodial lobes, and often have dorsal sediment tubercles. The revision of all type and non-type materials resultedin the distinction of five body patterns within Flabelligera; they can be recognized on the basis of body shape, tunic de-velopment, parapodial position, notopodial alignment, and shape of neurohooks. Flabelligera is restricted and four generaare proposed: Annenkova (neurohooks with crests tapered, apparently segmented), Flabegraviera (notopodia in laterallydescending series, notochaetae and neurochaetae in cylindrical sheaths, markedly longer than body width), Flabehlersia(body fusiform, notopodia ventrolateral) and Flabesymbios (body papillae not covered by tunic, notopodia dorsal with papillae in fan-shaped pattern, neuropodia ventral). Flabelligera contains 16 species with three newly described and a re-placement name is proposed: F. haswelli n. n. pro F. affine Haswell, F. nuniezi n. sp. from the Northeastern Atlantic andMediterranean Sea, F. orensanzi n. sp. from the Southwestern Atlantic, and F. salazarae n. sp. from the Eastern tropicalPacific. Annenkova is monotypic: A. mastigophora (Annenkova, 1952) n. comb. from the Northwestern Pacific. Flabe-graviera contains F. mundata (Gravier, 1906) n. comb. and F. profunda n. sp. both from the Antarctic. Flabehlersia in-cludes two species: F. induta (Ehlers, 1897) n. comb. from Tierra del Fuego and F. persimilis (Annenkova-Chlopina 1924)n. comb. from the Northwestern Pacific. Flabesymbios contains two species living on Northeastern Pacific sea-urchins: F. commensalis (Moore, 1909) n. comb. on Strongylocentrotus and F. roberti n. sp. on Centrostephanus.